2017
DOI: 10.1021/acs.inorgchem.6b02624
|View full text |Cite
|
Sign up to set email alerts
|

π-Expansive Heteroleptic Ruthenium(II) Complexes as Reverse Saturable Absorbers and Photosensitizers for Photodynamic Therapy

Abstract: Five heteroleptic tris-diimine ruthenium(II) complexes [RuL(N^N)](PF) (where L is 3,8-di(benzothiazolylfluorenyl)-1,10-phenanthroline and N^N is 2,2'-bipyridine (bpy) (1), 1,10-phenanthroline (phen) (2), 1,4,8,9-tetraazatriphenylene (tatp) (3), dipyrido[3,2-a:2',3'-c]phenazine (dppz) (4), or benzo[i]dipyrido[3,2-a:2',3'-c]phenazine (dppn) (5), respectively) were synthesized. The influence of π-conjugation of the ancillary ligands (N^N) on the photophysical properties of the complexes was investigated by spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 82 publications
7
52
0
Order By: Relevance
“…[9][10][11][12][13][14] As a highly investigated class of compounds, [Ru(phen)3] 2+ derivatives have been studied as PDT PSs. [15][16][17][18] Several examples have shown that the photophysical properties, including absorption, emission as well as excited states lifetimes can be influenced by choice of the coordinated ligands. [5,9,11,13,19] Next to suitable photophysical properties, the biological abilities of a PS including, for example, cellular localisation or mechanism of cellular uptake, play a predominant role in the efficiency of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] As a highly investigated class of compounds, [Ru(phen)3] 2+ derivatives have been studied as PDT PSs. [15][16][17][18] Several examples have shown that the photophysical properties, including absorption, emission as well as excited states lifetimes can be influenced by choice of the coordinated ligands. [5,9,11,13,19] Next to suitable photophysical properties, the biological abilities of a PS including, for example, cellular localisation or mechanism of cellular uptake, play a predominant role in the efficiency of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their unique photophysical and photochemical properties, polypyridyl ruthenium(II) complexes have found many applications in the fields of supramolecular, bio‐inorganic, and catalytic chemistry . Although many heteroleptic polypyridyl ruthenium(II) complexes have been synthesized and investigated, most are of the [Ru(N‐N) 2 (N′‐N′)] 2+ type, in which N‐N and N′‐N′ are bidentate ligands such as 2,2′‐bipyridyl (bpy), 1,10‐phenanthroline (phen), or their analogues , . The limited range of target complexes is related to the easy synthetic access to cis ‐[RuCl 2 (bpy) 2 ] (commercially available) and its analogue complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The development of PDT technology can aid in the fight against a range of diseases, such as tumors of the colon and bladder, tumors of the brain and spinal cord, and to develop new methods of treatment of skin in plastic surgery and cosmetology [ 46 , 47 ]. Positive results of treatment of proinflammatory diseases by photodynamic therapy show high efficiency of this method in respect of aerobic, facultative, and obligate anaerobic bacteria, and microscopic fungi [ 48 , 49 ].…”
Section: Recent Progress Of Photodynamic Therapymentioning
confidence: 99%